BOOK REVIEW: Martin Puchner, „Lumea scrisă. Povești care au schimbat oamenii, istoria și civilizația” [“The written world. Stories that have changed people, history and civilization”], Iași, Polirom, 2018, 306 p., ISBN: 9789734667758 - GLĂVAN, Bianca Maria (Studia Universitatis Babeș-Bolyai Historia, 2018)
The passion for literature and the admiration for the creative power of man is shared with us by Martin Puchner, professor “Byron and Anita Wien” of English and compared literature at Harvard University. His various interests aimed at modernism, drama, literary theory and universal literature and his power of expertise in this field have generated consecrated books: the bestseller in six volumes “The Norton Anthology of World Literature” (2012), “The Drama of Ideas” (2010), “The Norton Anthology of Drama” (2009), “Modern Drama: Critical Concepts” (2008) etc., plus the courses of HarvardX MOOC (online open courses). In the recent book of the professor, “The Written World: The Power of Stories to Shape People, History, Civilization”, we distinguish the effort to present the essentialized overview of literature history, a complex image because of temporal and spatial inclusion as well as the wider significance of the notion of literature. Thus, Puchner removes literature from the template of fiction and adds to it the political texts (such as US Declaration of Independence) and the religious texts (Buddhist sutras, the Bible). The 16 fundamental texts subjected to analysis by the author are not picked at random, but they represent true cultural references, written stories with the highest impact in the history of mankind. They are defining texts, with power to shape the way in which different cultures highlight their origins and values.